Fraud of Financial Statements at Listed Enterprises on Ho Chi Minh City Securities Department - Tien Hung, Nguyen; Sau, Huynh Van; Dung, Nguyen Tri (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2018)
The study was conducted to identify fraudulent financial statements at listed companies (DNNY) on the Ho Chi Minh City Stock Exchange (HOSE) through the Triangular Fraud Platform This is a test of VSA 240. At the same time, the conformity assessment of this model in the Vietnamese market. The results show that the model is based on two factors: the ratio of sales to total assets and return on assets; an Opportunity Factor (Education Level); and two factors Attitude (change of independent auditors and opinion of independent auditors). This model is capable of accurately forecasting more than 78% of surveyed sample businesses and nearly 72% forecasts for non-research firms.